2014
DOI: 10.3926/ic.470
|View full text |Cite
|
Sign up to set email alerts
|

Important motivators for buying green products

Abstract: Purpose: To addresses the main motivators that influence customers to buy green products as well as well as profiling the decisions that shape their behavior.Design/methodology/approach: The authors have conducted a review of the major research related to consumers to identify motivational factors, to draw conclusions about their impact on buying green products. Factor analysis is conducted on the collected data to find the underlying factors that motivate consumers to buy green products and most importantly m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 35 publications
(30 reference statements)
4
23
0
3
Order By: Relevance
“…Since, the Green industry helps developing countries to secure resource efficient low-carbon growth that creates new jobs, while protecting the environment (UNIDO, 2010). While several studies have already concluded that green products, products produced in an eco-friendly way or green industry's product are globally gaining acceptance among both the buyers and consumer groups and consumers are even willing to pay more for the products (Sehgal and Singh, 2010;Kianpour et al 2014;Kumar and Ghodeswar, 2015).…”
Section: Environmentally Friendly Factorymentioning
confidence: 99%
“…Since, the Green industry helps developing countries to secure resource efficient low-carbon growth that creates new jobs, while protecting the environment (UNIDO, 2010). While several studies have already concluded that green products, products produced in an eco-friendly way or green industry's product are globally gaining acceptance among both the buyers and consumer groups and consumers are even willing to pay more for the products (Sehgal and Singh, 2010;Kianpour et al 2014;Kumar and Ghodeswar, 2015).…”
Section: Environmentally Friendly Factorymentioning
confidence: 99%
“…It is also possible to learn what a specific customer does within a store by observation [10]. Thus, it is necessary for organizations to learn customers' behavior, including what steers them toward green purchasing [86].…”
Section: Customers' Purchasing Behaviorsmentioning
confidence: 99%
“…Various researchers have highlighted that customers perceive environmental problems in the way that they are described in the media and these environmental problems can influence their attitudes towards the adoption of green products (Moser and Uzzell 2003;Cherian and Jacob 2012;Kim 2011;Kianpour et al 2014;Majlath 2010). In a similar vein, Pahl et al (2005) and Milfont (2007) have supported that the perceived seriousness of environmental problems has a positive impact on consumers' attitudes to propel ecological behaviours as suggested by Tan (2011).…”
Section: Literature Review and Hypothesis Development Perceived Seriomentioning
confidence: 99%
“… The Role of government on the ecological adoption of products Numerous green marketing studies have depicted that government policies can influence the adoption of ecological products (Sinnappan and Rahman 2011;Chen and Chai 2010;Kianpour et al 2014). Likewise, Rezai et al (2013) have pointed out that the government can exert a significant role towards the adoption of green products through public campaigns, enforcement of laws and provision of environmental education to the general public.…”
Section: The Role Of Government and Adoption Of Ecological Productsmentioning
confidence: 99%
See 1 more Smart Citation